Expression Of Personal Deixis In Uzbek And French Languages - Ishanjanova Munosibxon Saidahmadovna; Kabilov Ulugbek Madaminovich (Zien Journals, 2022)
This article deals the types of deixis and their features in communication. In functional grammar emphasis the category of personality is a more significant part of categories, and it identifies with the methods of expressing the category of personality. In French language is characterized by the flection of verbs, personal pronouns and in the Uzbek language with suplektiv forms of the verb paradigm "bo’lmoq", and personal, possessive pronouns
Keywords: personality; category of persons; functional-semantic category; deixis